2013
DOI: 10.1530/eje-12-0849
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of hypopituitarism after subarachnoid haemorrhage using confirmatory testing and with BMI-specific GH cut-off levels

Abstract: Objective: Hypopituitarism following subarachnoid haemorrhage (SAH) has been reported to be a frequent occurrence. However, there is considerable heterogeneity between studies with differing patient populations and treatment modalities and most importantly employing differing endocrine protocols and (normal) reference ranges of GH. We aimed to examine prospectively a cohort of SAH survivors for development of hypopituitarism post-SAH using rigorous endocrine testing and compare GH response to glucagon stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
21
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
(36 reference statements)
11
21
1
Order By: Relevance
“…This was also found to be the case in the 12 month post-SAH evaluation by Gardner et al [16] The strength of our study is the prospective design, the broad endocrine evaluation and the correlation of endocrine disturbances to clinical characteristics of SAH.…”
Section: Pituitary Dysfunction In Relation To Sah Featuressupporting
confidence: 77%
See 1 more Smart Citation
“…This was also found to be the case in the 12 month post-SAH evaluation by Gardner et al [16] The strength of our study is the prospective design, the broad endocrine evaluation and the correlation of endocrine disturbances to clinical characteristics of SAH.…”
Section: Pituitary Dysfunction In Relation To Sah Featuressupporting
confidence: 77%
“…This prevalence of endocrine disturbances is consistent with previous studies by Dimoupolou et al, [10] Kreitschmann-Andermahr et al, [25] Aimaretti et al [3] and Tanriverdi et al [31] (37.5-68.2% prevalence at follow-up), but contrasts to results from Klose et al [24] and Lammert et al [26] who found few or no abnormalities at confirmatory testing. Gardner et al [16] recently reported 12% hypopituitarism in their patient series, however also with nonaneurysmal SAH patients included. The German Database on Hypopituitarism after Traumatic Brain Injury and Aneurysmal Subarachnoid Hemorrhage has also revealed a similar incidence of pituitary dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, results of several dynamic function tests are dependent on the BMI of the patient (23), therefore confounding the data.…”
Section: Introductionmentioning
confidence: 99%
“…Both TBI and non-TBI may be complicated by short-and long-term pituitary dysfunction, which has possible implications for the recovery and functional outcomes of patients (3). The reported prevalence of acute and chronic chronic subdural haematoma (12) and ischaemic stroke (13), have been related to an increased prevalence of hypopituitarism in some studies but not in others (14,15).…”
Section: Introductionmentioning
confidence: 99%